Making Use of Flashcards In Teaching English Vocabulary In Southern Region of Sumatera - Iman, Jaya Nur (STMIK Royal, 2025)
Vocabulary mastery is essential to young learners in learning English. This activity of community service was aimed at utilizing flashcards in English vocabulary instruction. A convenient sample of thirteen participants, mostly females between the ages of thirteen and eighteen, was chosen for this current activity. This was carried out in one of orphanages in Palembang, South Sumatera. To monitor and evaluate the degree of vocabulary achievement of the EFL learners, a vocabulary test was administered both before and after the intervention. The results indicated that the t obtained was much higher than the set t table and p value earned was much lower than .05. Therefore, it could be concluded that using flashcards significantly accelerated the acquisition of English vocabulary by young learners. Lastly, some fruitful implication were directed to future facilitators, researchers, and young learners, as participants.Keywords: flashcards; teaching; English vocabulary; young learners Abstrak: Penguasaan kosakata sangat penting bagi pelajar muda dalam mempelajari bahasa Inggris. Kegiatan pengabdian masyarakat ini ditujukan untuk memanfaatkan kartu flash dalam pengajaran kosakata bahasa Inggris. Sampel yang terdiri dari tiga belas peserta, sebagian besar perempuan berusia antara tiga belas dan delapan belas tahun, dipilih untuk kegiatan saat ini. Kegiatan ini dilaksanakan di salah satu panti asuhan di Palembang, Sumatera Selatan. Untuk memantau dan mengevaluasi tingkat pencapaian kosakata pelajar EFL, tes kosakata diberikan sebelum dan sesudah intervensi. Hasilnya menunjukkan bahwa nilai t yang diperoleh jauh lebih tinggi daripada t tabel yang ditetapkan dan nilai p yang diperoleh jauh lebih rendah dari .05. Oleh karena itu, dapat disimpulkan bahwa penggunaan kartu flash secara signifikan mempercepat perolehan kosakata bahasa Inggris oleh pelajar muda. Terakhir, beberapa implikasi yang bermanfaat ditujukan di masa mendatang kepada fasilitator, peneliti, dan pelajar muda, sebagai peserta.Kata kunci: kartu flash; pengajaran; kosakata bahasa Inggris; pelajar muda